A complex hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeting delivery technology and a process thereof
Patent Information
- Application Number
- CN202611015685.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-09
AI Technical Summary
[0005]因此,本发明提供了一种通过多级程序性释放与肠道靶向递送技术制备的复合降糖功能因子及其工艺,解决现有宠物糖尿病管理中血糖波动大及机体机能衰退的综合性治疗难题
[0016]The beneficial effects of this invention are as follows: This invention innovatively constructs a dual interpenetrating network structure consisting of a microscopic nanocore and a macroscopic gel shell, achieving multi-level programmed precise release through gastric protection, intestinal barrier, and mucosal targeting. Through the pH-responsiveness of the outer layer of calcium alginate gel, it effectively shields against gastric acid erosion and rapidly releases β-glucan in the intestine to construct a physical sugar-controlling barrier; the inner layer of chitosan nanoclusters utilizes its positive charge properties to target and adhere to the intestinal mucosa, deeply and slowly releasing ginsenosides and trace elements to regulate metabolism and repair functions. This process cleverly solves the pain points of poor stability and low absorption rate of active ingredients and the difficulty in processing physical barrier agents, achieving a dual synergistic effect of physical barrier and physiological regulation, significantly improving the overall hypoglycemic efficacy and bioavailability.
Smart Images

Figure CN122516113B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biopharmaceutical manufacturing, specifically to a compound hypoglycemic functional factor and its process prepared by multi-stage programmed release and intestinal targeted delivery technology. Background Technology
[0002] With changes in the lifestyles and diets of companion animals, the incidence of diabetes in pets (especially dogs and cats) is showing a significant upward trend and has become one of the major metabolic diseases seriously threatening the health and lifespan of pets. Compared with human diabetes, pet diabetes differs significantly in its pathological mechanisms and clinical management. Dogs mostly exhibit insulin-dependent characteristics, while cats, although mostly insulin-resistant, often have irreversible pancreatic function damage at the time of diagnosis. In addition, animals generally have a faster metabolic rate than humans and cannot perform precise active dietary control and high-frequency real-time blood glucose monitoring like humans, resulting in their postprandial blood glucose being prone to drastic fluctuations and making it difficult to maintain a stable state throughout the day.
[0003] Furthermore, veterinary diabetes is not simply a matter of abnormal blood glucose levels. Its course is often accompanied by severe osmotic diuresis (polyuria), leading to a significant loss of water-soluble vitamins, key coenzymes, and trace elements. This results in systemic functional decline, including increased oxidative stress, microcirculatory disturbances, weakened immunity, and reduced tissue repair capacity. Current conventional treatments often focus on insulin replacement or basal glucose control, failing to effectively block postprandial spikes in blood glucose levels while simultaneously providing deep nutritional repair for long-term damage. Therefore, reversing functional decline while controlling drastic blood glucose fluctuations remains a complex and pressing challenge in veterinary medicine. Summary of the Invention
[0004] In view of the aforementioned existing problems, the present invention is proposed.
[0005] Therefore, this invention provides a compound hypoglycemic functional factor and its process prepared by multi-stage programmed release and intestinal targeted delivery technology, which solves the comprehensive treatment problem of large blood glucose fluctuations and declining bodily functions in the current management of pet diabetes.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides a process for preparing a compound hypoglycemic functional factor using multi-stage programmed release and intestinal targeted delivery technology, comprising the following steps: S1. Dissolve 70-90 parts by weight of chitosan to prepare a cationic matrix solution, then add 20-40 parts by weight of ginseng extract and premixed trace element combination; ultrasonically disperse at 200-400W power for 25-35 minutes to embed the active ingredients into the chitosan chain; then add an induction solution to self-assemble into a drug-loaded nanocluster dispersion. S2. Take 220-260 parts by weight of sodium alginate and 350-450 parts by weight of β-glucan, dissolve them together in deionized water, and stir at a constant temperature of 45-55℃ for 1-3 hours to form an interpenetrating network matrix solution; after the solution cools to below 35℃, add compound vitamin powder and then inject it into the drug-loaded nanocluster dispersion, and shear and mix to form a uniform composite colloidal solution; S3. The composite colloidal liquid is atomized and extruded into a crosslinking bath containing calcium chloride at 2~6℃ for 15~21 minutes. The coordination and crosslinking of calcium ions and sodium alginate will form a dense gel shell on the surface of the droplet, sealing the internal components and forming wet gel microspheres. S4. Take out and clean the wet gel microspheres, remove the moisture by vacuum freeze-drying while retaining the porous mesh structure inside the microspheres, and obtain the composite hypoglycemic functional factor.
[0007] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology described in this invention, the premixed trace element combination is composed of zinc lactate, chromium picolinate and selenium-enriched yeast mixed in a mass ratio of 20~24:3~5:0.5~1.5.
[0008] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to the present invention, wherein: the induction solution is sodium tripolyphosphate solution, the amount of chitosan is 80 parts by weight, and the amount of ginseng extract is 30 parts by weight.
[0009] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to the present invention, the amount of sodium alginate is 240 parts by weight and the amount of β-glucan is 400 parts by weight.
[0010] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-level programmed release and intestinal targeted delivery technology according to the present invention, the ultrasonic power in the ultrasonic dispersion process is 300W and the processing time is 30 minutes; the preparation temperature of the interpenetrating network matrix solution is 45~55℃ and the stirring time is 1~3 hours.
[0011] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to the present invention, wherein: the microfluidic granulation device adopts a coaxial nozzle, the outer fluid is a high-pressure pulsed gas, including nitrogen and argon; the inner fluid is the compound colloidal liquid; and the concentration of calcium chloride in the crosslinking bath is 2wt%~4wt%.
[0012] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to the present invention, the cross-linking time is 18 minutes; the cleaning medium for the microspheres after cross-linking is sterile deionized water, and the number of cleaning times is not less than 3.
[0013] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to the present invention, the specific procedure of the vacuum freeze-drying is as follows: pre-freezing at -45~-35℃ for 3~5 hours; then sublimation drying at a vacuum degree of 10~300Pa and a shelf temperature of -20~-5℃ for 20~30 hours; and finally desorption drying at a shelf temperature of 20~30℃ for 3~5 hours.
[0014] As a preferred embodiment of the preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology described in this invention, the compound vitamin powder is premixed from B vitamins and vitamin C at a mass ratio of 1:1.5~2.5, and the amount added is 40~60 parts by mass.
[0015] This invention also provides a composite hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology, which is prepared by the above-mentioned preparation process. The prepared composite hypoglycemic functional factor has a core-shell structure combining macroscopic microspheres and microscopic nanoclusters. The outer layer is a pH-sensitive hydrogel network formed by calcium alginate and β-glucan, which remains contracted and dense in the gastric acid environment and swells and disintegrates in the intestinal fluid environment to release β-glucan and vitamins. The inner layer is a chitosan drug-loaded nanocluster dispersed in the outer matrix. The surface of the cluster is coated with ginseng extract and trace elements, which can adhere to the intestinal mucosa and achieve sustained release of active ingredients.
[0016] The beneficial effects of this invention are as follows: This invention innovatively constructs a dual interpenetrating network structure consisting of a microscopic nanocore and a macroscopic gel shell, achieving multi-level programmed precise release through gastric protection, intestinal barrier, and mucosal targeting. Through the pH-responsiveness of the outer layer of calcium alginate gel, it effectively shields against gastric acid erosion and rapidly releases β-glucan in the intestine to construct a physical sugar-controlling barrier; the inner layer of chitosan nanoclusters utilizes its positive charge properties to target and adhere to the intestinal mucosa, deeply and slowly releasing ginsenosides and trace elements to regulate metabolism and repair functions. This process cleverly solves the pain points of poor stability and low absorption rate of active ingredients and the difficulty in processing physical barrier agents, achieving a dual synergistic effect of physical barrier and physiological regulation, significantly improving the overall hypoglycemic efficacy and bioavailability. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 The results of the trace element synergistic ratio screening test are shown in the figure. Figure 2 The graph shows the blood glucose test results from the screening experiment for the optimal functional dosage of β-glucan. Figure 3 Figure 1 shows the results of the screening experiment on the process ratio of the outer skeleton and the filling matrix. Figure 4 Figure showing the results of the screening experiment for the formulation of the inner drug delivery system; Figure 5 Figure 1 shows the experimental test results for optimizing ultrasonic processing parameters. Figure 6 Figure 1 shows the experimental test results of the outer matrix dissolution and primary crosslinking process optimization. Figure 7 The figure shows the test results of the cross-linking molding time screening experiment; Figure 8 This is a process flow diagram of the compound hypoglycemic functional factor prepared by the present invention through multi-stage programmed release and intestinal targeted delivery technology. Detailed Implementation
[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0020] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "one embodiment" or "example" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the invention. The appearance of an embodiment in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that mutually excludes other embodiments.
[0022] The β-glucan used in this invention is Celec® β-glucan produced by Sichuan Hetai Xinguang Biotechnology Co., Ltd. It is a repeating unit chain structure connected by 7 β-1,3 glycosidic bonds and 2 α-1,3 glycosidic bonds, without side chains.
[0023] Example 1
[0024] This embodiment aims to select the core ingredient combination with the best comprehensive performance in regulating blood sugar, improving microcirculation, and nutritional repair from a large number of functional raw materials through a series of scientific and systematic screening experiments, targeting the complex physiological and metabolic needs of people with high blood sugar.
[0025] 1.1 Screening experiment for effective hypoglycemic components
[0026] Elevated blood glucose levels are a complex physiological process involving three core stages: first, the hydrolysis of carbohydrates in food into glucose by digestive enzymes (the production stage); second, the release of glucose through the intestinal mucosa into the bloodstream (the absorption stage); and third, the uptake and oxidation of glucose in the blood by the body's cells (the metabolism stage). Therefore, an ideal hypoglycemic agent should play a significant regulatory role in at least one or more of these stages.
[0027] Experimental groups: Group A1 (mulberry leaf extract) was standardized to 5% 1-deoxynojirimycin (DNJ) content, with a concentration of 2.0 mg / mL; Group A2 (bitter melon polypeptide) has a polypeptide content >80% and is prepared at a concentration of 1.5 mg / mL; Group A3 (L-arabinose) has a purity of >99% and is prepared at a concentration of 20 mg / mL; Group A4 (konjac glucomannan) has a viscosity >30000 mPa·s and a prepared concentration of 0.5% (this is its operating limit concentration due to its excessively high viscosity). Group A5 (chromium pyridinecarboxylate) has a chromium content of 12%, which translates to a chromium element concentration of 100 μg / mL. Group A6 (β-glucan) has a molecular weight >200kDa and is prepared at a concentration of 1.0%.
[0028] Add the sample solution and α-glucosidase solution (0.2 U / mL) to a 96-well plate, incubate at 37°C for 10 minutes, then add the substrate p-nitrobenzene-α-D-glucopyranoside (pNPG). The enzymatic reaction will generate yellow p-nitrophenol (pNP). After 20 minutes of reaction, add sodium carbonate to terminate the reaction. Measure the absorbance at 405 nm using an ELISA reader. α-glucosidase is a key enzyme in the small intestine responsible for breaking down disaccharides and oligosaccharides into monosaccharides. The stronger its activity is inhibited, the more effectively the source of postprandial blood glucose production is intercepted.
[0029] The sample mixture containing 100 mmol / L glucose was placed into a dialysis bag with a molecular weight cutoff of 12000 Da. After the two ends were tied tightly, the bag was immersed in a beaker containing deionized water and shaken at 100 rpm in a constant temperature water bath at 37°C. Every 30 minutes, a sample was taken from the dialysate outside the dialysis bag to determine the glucose content. The glucose dialysis delay index (GDRI, %) at 60 minutes was calculated. The higher the GDRI value, the more significant the physical barrier and retention effect of this component on glucose.
[0030] Insulin-resistant mouse liver cancer cells (Hepa1-6) that were successfully induced were seeded into culture plates, and the test sample was added and cultured for 24 hours. Then, the glucose content remaining in the culture medium was measured by glucose oxidase method, and the increase rate of glucose consumption of cells relative to the model group was calculated. The higher the increase rate, the stronger the biological activity of improving glucose metabolism and lowering blood sugar.
[0031] The test results are as follows: Table 1
[0032] Among them, mulberry leaf extract showed high enzyme inhibition rate, making it the best at source interception, but it lacked physical barrier and metabolic regulation capabilities; bitter melon peptides and chromium picolinate performed well in the metabolic process, but were ineffective against physical barriers and the peptides were easily inactivated; konjac glucomannan had the best physical barrier, but its gel properties led to serious processing obstacles. β-glucan showed excellent absorption barrier performance and possessed certain enzyme inhibition capabilities, covering both the generation and absorption stages simultaneously. Most importantly, it combined excellent physiological barrier function with good process adaptability. Therefore, β-glucan was selected as the core hypoglycemic component.
[0033] 1.2 Screening experiment for replenishing lost nutrients
[0034] Given that diabetic patients often experience polydipsia and polyuria, which can lead to excessive excretion of water-soluble vitamins and minerals, long-term deficiency will exacerbate metabolic disorders. To enhance the overall efficacy of the product, this formulation proposes to supplement the core hypoglycemic component (β-glucan) with B vitamins, vitamin C, and chromium picolinate, which has been shown to have significant metabolic regulatory functions in experiment 1.1, as a chromium supplement. Zinc, as a key cofactor in insulin synthesis and secretion, is crucial for maintaining blood glucose homeostasis.
[0035] Five representative zinc supplements—zinc sulfate, zinc gluconate, zinc glycinate, zinc oxide, and zinc lactate—were selected and prepared into solutions with the same zinc elemental concentration (equivalent to 10 mg / L zinc content). A mouse small intestinal epithelial cell (IEC-6) monolayer model was used to simulate the transport process of small intestinal epithelial cells. The zinc solution to be tested was added to the apical side (simulating the intestinal lumen) of the cell model. After culturing for 2 hours, the zinc concentration on the basal side (simulating blood) was measured, and the apparent permeability coefficient (Papp) was calculated to reflect the bioavailability of zinc. Each group of samples was placed in simulated gastric fluid (pH 1.2), and the zinc ion dissolution rate curve was measured within the first 15 minutes. The smoother the dissolution, the smaller the instantaneous ionic impact on the gastric wall and the lower the irritation.
[0036] The test results are as follows: Table 2
[0037] Among the zinc supplements, zinc glycinate has the highest absorption rate and moderate dissolution rate, but its high cost limits its use. Zinc gluconate has a high absorption rate, but its rapid release can easily cause stomach irritation. Ultimately, zinc lactate, which also has a sustained-release effect, a high absorption rate, and is more economical, was chosen as the zinc supplement.
[0038] 1.3 Screening experiment for pancreatic islet protective components
[0039] During the progression of diabetes, a prolonged hyperglycemic environment induces pancreatic β-cells to produce large amounts of reactive oxygen species (ROS). This oxidative stress is a core cause of pancreatic islet dysfunction and even apoptosis. To construct a complete intervention chain of source interception (blood sugar reduction), exogenous supplementation (nutrition), and endogenous protection (organs), this experiment aims to screen for a component that can effectively protect pancreatic islet cells.
[0040] Vitamin E, tea polyphenol EGCG, coenzyme Q10, lipoic acid, copper gluconate, and selenium-enriched yeast were all formulated to concentrations with equivalent antioxidant activity for comparative experiments.
[0041] The ferric reducing power method (FRAP) was used to determine the reductive properties of each component under acidic conditions. Restored to blue The ability to directly scavenge free radicals at the chemical level is reflected in the ability of each substance to do so. The solutions were placed in simulated gastric juice (pH 1.2) and simulated intestinal juice (pH 6.8) and shaken for 4 hours in an aerobic environment at 37°C. The retention rate of the effective components before and after treatment was measured.
[0042] Mouse pancreatic islet tumor cells (MIN6) were cultured in 33 mM high-glucose medium for 48 hours to induce oxidative damage. Protective agents were added to each group during this period. After treatment, cells were stimulated with low-glucose (2.8 mM) and high-glucose (16.7 mM) Krebs solutions, respectively, and glucose-stimulated insulin secretion (GSIS) was measured. This was used to assess the protective agents' ability to repair pancreatic β-cell damage.
[0043] The test results are as follows: Table 3
[0044] Among them, tea polyphenols and lipoic acid have excellent antioxidant capabilities, and the secretion of lipoic acid is also higher. However, the low retention rate means that most of the active ingredients have been oxidized and inactivated before reaching the site of action. Copper gluconate and vitamin E have high retention rates, but their impact on secretion is limited. Selenium-enriched yeast has excellent overall capabilities, thus serving as the final pancreatic islet protection component.
[0045] 1.4 Screening Experiment for Organism Function Repair Components
[0046] Diabetes is essentially a chronic, systemic wasting disease. The body is chronically in a state of high glucose toxicity and negative nitrogen balance, which easily leads to impaired tissue repair capabilities (such as slow-healing skin ulcers and microvascular complications), chronic low-grade inflammation, and organ dysfunction. Therefore, in addition to lowering blood sugar and protecting the pancreas, there is an urgent need to introduce a systemic repair component that can promote cell regeneration, regulate immune inflammation balance, and is suitable for oral administration.
[0047] The selected functional ingredients are representative of tissue repair and functional regulation: epidermal growth factor (EGF), lactoferrin, curcumin, squalene, silymarin, and ginseng extract.
[0048] A physical injury model was constructed using mouse fibroblasts (L929). Standard scratches were created on a monolayer of cells, and each component was added and cultured for 24 hours. The percentage of healed area in the scratched region was observed and calculated under a microscope. This indicator provides a direct observation of the component's ability to promote cell migration and proliferation and accelerate tissue physical repair. Lipopolysaccharide (LPS) was used to induce an inflammatory response in mouse macrophages (RAW264.7). The concentration of nitric oxide (NO) in the culture medium was measured. Chronic inflammation hinders tissue repair; inhibiting NO production suggests the creation of a low-inflammatory, benign repair microenvironment for the body. Each solution was incubated in simulated gastric juice (pH 1.2, containing pepsin) for 2 hours, and its residual activity was then measured to eliminate components that were effective in vitro but ineffective orally.
[0049] The test results are as follows: Table 4
[0050] Among them, epidermal growth factor has outstanding repair capabilities, but its inflammation suppression rate and survival rate are extremely low; curcumin has high inflammation suppression rate and survival rate, but its wound healing ability is low. Ginseng extract, on the other hand, has a high retention rate and excellent comprehensive capabilities in wound healing and inflammation suppression, thus making it a suitable component for repairing bodily functions.
[0051] Example 2
[0052] Reference Figures 1 to 4 This is the second embodiment of the present invention. This embodiment aims to construct a delivery carrier system capable of carrying the functional components obtained from the screening process described above. Although the selected core components (such as β-glucan, ginseng extract, etc.) possess a certain degree of physicochemical stability, after oral ingestion, they still face the erosion of the highly acidic environment of the stomach and the potential degradation risk from digestive enzymes. To ensure that each functional factor can completely pass through the gastric region and achieve release under the specific physiological environment of the intestine, this embodiment will establish a microcapsule matrix matrix with suitable mechanical strength and environmental responsiveness, as well as its preparation process, through experimental screening.
[0053] 2.1 Screening Experiment of Inner Core Carrier Material
[0054] To achieve deep absorption of functional factors (especially ginsenosides and trace elements) in the intestine, the inner core carrier not only needs excellent microencapsulation capabilities but, more importantly, must possess superior intestinal mucosal adhesion properties. The intestinal mucosa is covered by a mucus layer primarily composed of mucins, rich in sialic acid and sulfonic acid groups, and is generally negatively charged. Therefore, the core objective of this step is to screen a positively charged (cationic) natural polymer material with good biosafety to achieve bio-anchoring through electrostatic interactions.
[0055] Gelatin Type B, polylysine ε-PL, cationic starch, soy protein isolate SPI, guar gum, and chitosan were selected for testing.
[0056] In a simulated intestinal fluid environment (pH 6.5), the Zeta potential of each component particle was measured using a laser particle size and potential analyzer. The higher the positive potential value, the stronger the electrostatic affinity with the negatively charged mucosa, theoretically. A flushing-retention model was used. Fresh porcine small intestinal mucosa tissue was fixed in a rheological tank, and fluorescently labeled carrier solutions were added. After 5 minutes of static adsorption, the mucosa was continuously flushed with simulated intestinal fluid at a constant flow rate for 30 minutes. The fluorescence intensity of the mucosal surface before and after flushing was measured, and the retention rate was calculated to detect the carrier's ability to adhere to the intestinal wall under peristaltic conditions. Using ginseng total saponins as a model drug, drug-loaded microparticles were constructed. After centrifugation, the content of free drug in the supernatant was measured, and the encapsulation amount was calculated to assess the carrier's ability to form a dense core structure and lock in the active ingredient.
[0057] The test results are as follows: Table 5
[0058] Polylysine has a high potential and good adsorption effect, but as a short-chain polypeptide, its molecular spatial network is extremely sparse, which cannot effectively encapsulate large ginsenoside molecules, resulting in low encapsulation capacity and making it unsuitable as a carrier. Cationic starch has a high encapsulation capacity, but its retention rate is relatively low. Chitosan has excellent comprehensive capabilities, so as a cationic polymer, it is used to load minerals and ginsenosides.
[0059] 2.2 Screening Experiment for pH-Sensitive Protective Matrix in Outer Layer
[0060] The core objective of constructing the outer matrix of microcapsules is to achieve intelligent environmental response, namely, to maintain a dense structure in acidic gastric juice (pH 1.2) to protect the inner active ingredients, and to rapidly swell and disintegrate in weakly alkaline intestinal juice (pH 6.8) to release functional factors.
[0061] Considering that the inner chitosan layer is positively charged, matrices that are also positively charged were excluded from the experimental design. The selected anionic polysaccharides included low-ester pectin, κ-carrageenan, and sodium alginate, while the nonionic polysaccharides included agar, konjac gum, and methyl cellulose (MC).
[0062] Each matrix solution was mixed with an equal volume of inner chitosan dispersion, sheared at 3000 rpm, and allowed to stand for 2 hours. The mixture was then observed for stratification, flocculation, or precipitation; a homogeneous and stable system is a prerequisite for microsphere formation. Microfluidic technology was used to prepare gel microspheres from the mixture. These microspheres were placed in simulated gastric fluid (pH 1.2) and shaken for 2 hours. The concentration of tracer (ginsenosides) in the supernatant was measured; a lower concentration indicates stronger shielding protection in an acidic environment. The gastric fluid-treated microspheres were then transferred to simulated intestinal fluid (pH 6.8), and the time required for the microspheres to completely disintegrate (or release >80% of their contents) from an intact particle state was recorded.
[0063] The test results are as follows: Table 6
[0064] Among them, the non-ionic group all exhibited varying degrees of interfacial stratification. This was due to their inability to generate electrostatic attraction with the positively charged chitosan core, causing the two phases to separate upon standing, severely affecting the quality of the pellets. Although carrageenan has good gastric protection, its slow disintegration in intestinal fluid prevents the release of active ingredients. Therefore, sodium alginate was chosen as the optimal choice for the outer protective matrix.
[0065] 2.3 Raw material ratio optimization experiment
[0066] Having clarified the complex functional component system based on β-glucan and ginseng extract, combined with zinc lactate, chromium picolinate, and selenium-enriched yeast through the aforementioned experiments, and having screened chitosan and sodium alginate as bilayer delivery carriers, this embodiment will conduct a series of systematic ratio optimization experiments to achieve the dual optimization of the final product in terms of physiological function and preparation process.
[0067] 2.3.1 Screening for synergistic ratio of trace elements
[0068] Given that the theoretical addition amounts (micrograms to milligrams) of zinc lactate, chromium picolinate, and selenium-enriched yeast in the overall formulation are significantly lower than those of β-glucan and ginseng extract (grams), and considering the complex physiological synergistic or antagonistic effects among trace elements (such as zinc-selenium interaction and chromium-zinc metabolic linkages), prioritizing the determination of the optimal internal ratio among these three is a prerequisite for constructing a steady-state formulation.
[0069] To ensure the scientific rigor of in vitro cell screening experiments, it is first necessary to determine the upper limit of the cells' tolerance to each trace element. Mouse small intestinal epithelial cells (IEC-6) were used as a model, and 5 × 10⁶ cells were seeded per well in a 96-well plate. 3Cells were cultured in DMEM medium (200 μL per well) containing 10% fetal bovine serum. The cytotoxicity threshold of each component was determined through preliminary experiments, and the highest concentration that maintained cell viability >95% was defined as the theoretical baseline amount per unit of that component.
[0070] The theoretical baseline amounts (UD) of each component in a 200 μL system were determined to be: zinc lactate (Zn) 3.0 μg / mL, chromium pyridinecarboxylate (Cr) 0.5 μg / mL, and selenium-enriched yeast (Se) 0.15 μg / mL.
[0071] To investigate the optimal synergistic ratio of the three trace elements within the upper limit of cellular common load, the total number of components in the mixture was set to 10, with each component representing 1 / 10 of the UD concentration of that component. This means that regardless of changes in the component ratios, the total metabolic load exerted on cells by the mixed solution is always kept within the theoretically safe upper limit.
[0072] After IEC-6 cells adhered, the culture medium was replaced with one containing 30 mM glucose and... A high-glucose oxidative stress combined injury model was constructed using culture medium. A trace element mixture prepared according to the designed ratio was added simultaneously, and the mixture was incubated for 24 hours.
[0073] The effectiveness of the formula was comprehensively evaluated by detecting glucose consumption, intracellular ROS content, and cell viability.
[0074] Test results are as follows Figure 1 As shown, by constructing a ternary spatial response surface model and solving for the extreme values, the peak coordinates of glucose consumption are (3.42, 4.65, 1.93), the valley coordinates of ROS content are (3.15, 2.12, 4.73), and the peak coordinates of cell viability are (4.28, 2.84, 2.88). Taking the arithmetic mean of the three, the theoretical ratio of Zn:Cr:Se is 3.62:3.20:3.18. Combining the baseline amount of each component, the actual mass ratio is converted to Zn:Cr:Se = 10.86:1.60:0.48. Considering the requirements of industrial formulation, a mass ratio of 23:4:1 is finally adopted.
[0075] 2.3.2 Screening for the optimal functional dosage of β-glucan
[0076] In the composite microsphere system of this invention, β-glucan is not used as the inner active ingredient tightly encapsulated by microcapsules, but is distributed in the outer matrix. This allows for rapid release after the microspheres disintegrate in the intestine, utilizing its high molecular weight to absorb water and swell, constructing a high-viscosity physical barrier to block the rapid absorption of glucose. Insufficient dosage results in insufficient viscosity in the intestinal lumen to form an effective filter, leading to poor blood glucose lowering effect; excessive dosage, while theoretically enhancing the barrier effect, can cause microfluidic granulation failure (nozzle blockage) due to excessive liquid viscosity, and may also induce gastrointestinal discomfort such as bloating in mice.
[0077] Based on relevant literature, the effective dose of β-glucan in rodents is typically between 200 and 1000 mg / kg. To cover the complete range from minimally effective to saturated doses, this experiment used db / db diabetic mice (type II diabetes model) weighing 40±5g as the model, and set the dosage range to 100 mg / kg to 1200 mg / kg, with a step size of 100 mg / kg.
[0078] Mice were divided into 12 groups of 10 mice each. Each group was administered β-glucan solution by gavage at the designed dose once daily for 7 consecutive days to improve the intestinal environment. After the last administration, the mice were fasted for 12 hours to empty their intestines, and then administered glucose (2 g / kg) by gavage. Blood glucose levels were measured at 0, 30, 60, and 120 minutes.
[0079] Test results are as follows Figure 2 As shown, with the increase of β-glucan dosage, the peak blood glucose level showed a significant downward trend. When the dosage exceeded a certain level, the decrease in blood glucose levels at each time point narrowed considerably, exhibiting a strong diminishing marginal effect. Through derivative calculations of the blood glucose reduction rate and dosage, the inflection point of marginal benefit appeared at approximately 780 mg / kg. To facilitate preparation and retain a certain functional margin, 800 mg / kg was ultimately determined as the optimal functional dosage.
[0080] 2.3.3 Screening of the process ratio for the outer skeleton and the filling matrix
[0081] β-glucan, as the core filler component of the outer layer of microspheres, directly determines the molding quality and barrier performance of microspheres in its ratio with the framework material (sodium alginate). If the proportion of sodium alginate is too low, the gel network will be sparse and unable to effectively lock in the contents, leading to gastric dissolution; if the proportion is too high, although the protective effect is enhanced, it will crowd out the space of functional components, and the dense gel shell may hinder rapid disintegration in the intestine.
[0082] To find the optimal balance between process and function, this experiment fixed the amount of β-glucan (set as 1 part) and adjusted the proportion of sodium alginate (0.3–1.0 parts), setting up a total of 8 gradient groups. To monitor structural integrity intuitively and with high sensitivity, the microspheres were coated only with highly water-soluble sodium fluorescein as a tracer.
[0083] The particle size distribution of wet microspheres was determined using dynamic light scattering (DLS). A smaller PDI value (<0.3) indicates that the microspheres are uniform in size and well-formed; a larger PDI value (>0.5) suggests the presence of broken fragments or agglomeration. The microspheres were placed in simulated gastric fluid at pH 1.2 and shaken for 2 hours. The fluorescence intensity of the supernatant was measured, and the leakage percentage was calculated.
[0084] Test results are as follows Figure 3 As shown, in the low-proportion range, insufficient skeleton material prevents the formation of a continuous gel network, resulting in a loose or even collapsed microsphere structure. This leads to an extremely high PDI value and significant leakage of the fluorescent tracer, failing to meet the basic requirements for acid resistance protection. In the high-proportion range, although the leakage rate further decreases with increasing sodium alginate concentration, the PDI value rebounds. This is because the excessively high polymer concentration causes a surge in the viscosity of the liquid, resulting in tailing and stringing during microfluidic jetting, affecting the sphericity and uniformity of the formed spheres. Considering both molding quality and protective effect, and to maximize the relative loading of the functional component (β-glucan), a sodium alginate:β-glucan ratio of 0.6:1 was ultimately selected as the standard process formulation for the outer matrix.
[0085] 2.3.4 Screening of Inner Layer Drug Delivery System Ratio
[0086] Having determined the ratio of the outer matrix (sodium alginate and β-glucan) and trace elements, this step aims to explore the optimal binding ratio between the core active ingredient (ginsenosides) and the inner carrier (chitosan). Since the amount of the trace element complex is extremely low (in milligrams), its space and charge occupancy on the chitosan carrier is negligible; therefore, the focus is on the binary interaction between ginsenosides and chitosan.
[0087] Based on the polyelectrolyte complexation theory and the sodium alginate dosage determined in experiment 2.3.3 (approximately 240g), and extrapolating from the empirical value of charge matching (sodium alginate:chitosan ≈ 3:1), the theoretical upper limit of chitosan binding is approximately 80g. Referring to the conventional drug loading ratio for nanoparticles (1:1~1:2), the theoretical upper limit of ginsenoside loading is approximately 40-80g. Considering the need for sodium alginate binding at the effluent sites, 40g is chosen. The upper limits of chitosan and ginsenoside dosage are set at 80g and 40g respectively, with eight uniform gradients for each. The fixed conditions are 240g sodium alginate and 400g β-glucan (scaled down to laboratory scale).
[0088] A corresponding amount of ginsenoside dispersion was added dropwise to a chitosan solution and ultrasonically dispersed for 30 minutes to form an inner suspension. Samples were taken, and the Zeta potential of the suspension was measured using a laser particle size potentiometer. The prepared suspension was injected into a sodium alginate solution for ionic cross-linking to form microspheres. The wet microspheres were separated by high-speed centrifugation at 10,000 rpm. The supernatant containing unencapsulated drug and unreacted polymers was discarded, and the bottom gel microsphere precipitate was collected. The precipitate was completely dissolved using a solvent demulsification method, and the absolute content of ginsenosides was determined by HPLC to assess the drug loading capacity. A quantitative amount of β-glucan solution (simulating the outer filling environment) was mixed into the separated microsphere system, and after redispersement, the PDI value of the microspheres was measured.
[0089] Test results are as follows Figure 4 As shown in the Zeta potential spectrum, the positive charge of the system is significantly shielded as the proportion of ginsenosides increases. When the potential drops below the critical value of +20mV (roughly distributed along the chitosan:ginsenoside = 1.5:1 ratio), the PDI data shows a cliff-like deterioration, indicating that chitosan can no longer provide enough grippers to anchor sodium alginate, leading to the disintegration of the microsphere structure. The effective binding data further confirms that the drug loading increases linearly with the amount of feed in the stable range of potential > +25mV, while it drops sharply in the disintegration zone. To achieve the highest drug loading efficiency while ensuring absolute structural stability, the critical region where PDI < 0.25 and the binding amount is at the peak of linear growth (i.e., chitosan: ginsenoside ≈ 2:1) was selected as 80g chitosan: 40g ginsenoside (i.e. 2:1). However, to leave a margin (safety margin), the ginsenoside content was reduced to 30g as the optimal process ratio for the inner layer drug loading system. At this point, the zeta potential of the microspheres was maintained at +20.89mV, and the effective binding amount per batch was 28.45g.
[0090] Example 3
[0091] refer to Figures 5 to 7 This is the third embodiment of the present invention. This embodiment aims to explore and establish the optimal process parameters for microsphere preparation. Based on the ionic cross-linking molding mechanism of alginate gel, the density and mechanical strength of its microstructure are typically affected by the cross-linking conditions. To achieve acid resistance protection and enteric release functionality, key process variables that may affect the microsphere structure and performance will be systematically screened and optimized experimentally to obtain a final product with stable physicochemical properties and release behavior as expected.
[0092] 3.1 Construction of Inner Membrane Adhesion-Type Nanocore Process Optimization
[0093] This step focuses on the preparation process of the inner drug-loaded nanocore. First, 80g of chitosan is dissolved in a sufficient amount of 1% acetic acid solution and stirred until a transparent and homogeneous cationic matrix solution is formed. Then, 30g of ginseng extract and a premixed trace element combination (in a ratio of 23:4:1) are added.
[0094] 3.1.1 Optimization of Ultrasonic Processing Parameters
[0095] To ensure that the active ingredients are deeply embedded in the microscopic polymer chain network of chitosan, rather than simply suspended at the macroscopic level, ultrasonic dispersion technology is commonly used in industry. However, the input of ultrasonic energy needs to be precisely controlled. If the power or time is insufficient, the coiled structure of the polymer chains cannot be effectively opened, resulting in uneven drug encapsulation; if the energy is too high, it may lead to the degradation of active ingredients (such as ginsenosides) or excessive breakage of chitosan chains, affecting the quality of subsequent nucleation.
[0096] The ultrasonic frequency was fixed at 40 kHz, and the ultrasonic power was tested from 100 W to 600 W in 100 W increments; the treatment time was tested from 10 min to 60 min in 10 min increments. In addition to the routine detection of zeta potential (characterizing charge exposure) and particle size distribution (PDI, characterizing dispersion uniformity), the transmittance stability of the dispersion was also tested. The ultrasonically treated dispersion was placed in a centrifuge tube and centrifuged at 3000 rpm for 10 minutes. The transmittance of the supernatant was measured at a wavelength of 600 nm. The higher the transmittance, the finer the dispersion of the poorly soluble ginseng extract, the more stable the colloidal system, and the absence of obvious agglomeration and precipitation.
[0097] Test results are as follows Figure 5 As shown, experimental data indicate that ultrasonic energy input exhibits typical threshold effects and overload damage characteristics. In the low-power range, even extended processing time fails to effectively reduce PDI or increase the Zeta potential, indicating insufficient energy to untangle molecular chain entanglements. Excessive power or time leads to a worsening of PDI rebound and a decrease in potential, suggesting polymer chain breakage or degradation and aggregation of active ingredients. In the medium-power range of 300–400 W, with time extended to approximately 30 minutes, all indicators reach their optimal equilibrium point, forming uniform and stable nanocores. Considering both energy efficiency and quality, 300 W power for 30 minutes was ultimately selected as the standard process.
[0098] 3.2 Optimization of outer matrix dissolution and primary crosslinking process
[0099] This step involves the connection between the inner and outer layers of the microspheres and the preparation of the outer matrix. First, sodium tripolyphosphate (CS:TPP mass ratio fixed at 5:1) is slowly added dropwise to the inner drug-loaded dispersion. Through electrostatic interaction, chitosan chains are induced to shrink and self-assemble into dense nanoclusters with a particle size of 200-500 nm, thereby locking in ginsenosides and minerals and endowing them with mucosal adhesion properties.
[0100] Next, a smart gel matrix to support β-glucan and vitamins needs to be constructed. Sodium alginate and β-glucan were dissolved in deionized water at the optimal ratio (0.6:1) determined in Example 2. Since the dissolution behavior of polysaccharides is highly dependent on thermal history, dissolution temperature and time are critical variables. If the temperature is too low or the time is insufficient, the polymer chains cannot fully extend, leading to solution heterogeneity and affecting subsequent spheroidization quality and pH responsiveness. If the temperature is too high or heating is prolonged, not only will energy consumption increase, but thermal degradation of the polysaccharide chains may also occur, reducing gel strength and viscosity.
[0101] The experimental temperature was set from 30 to 70℃ in 10℃ increments; the stirring time was set from 0.5h to 4h in 0.5h increments.
[0102] The viscosity of the solution after dissolution is measured using a rotational viscometer. Viscosity is a core indicator reflecting the degree of dissolution of polymers and the integrity of molecular chains. The more complete the dissolution, the higher the viscosity; if degradation occurs, the viscosity will decrease.
[0103] Each group of solutions was prepared into microspheres using a microfluidic device, and their sphericity was statistically analyzed. Poorly dissolved solutions tend to cause rough or tailed microsphere surfaces. Then, the mechanical strength of the formed microspheres was measured to evaluate the compactness of the matrix network.
[0104] Test results are as follows Figure 6 As shown, the experimental data clearly reveal the nonlinear effect of dissolution conditions on the properties of the polymer matrix. In the low-temperature region, due to the limited molecular thermal motion, even with an extended dissolution time of 4 hours, the viscosity and gel strength were still in the climbing stage and had not reached their optimal state. In the high-temperature region, although dissolution was rapid in the initial stage, after 1.5 to 2 hours, all indicators showed a significant decrease, confirming the thermal degradation effect of the polysaccharide chains, which led to a significant impairment in the sphericity and mechanical strength of the microspheres.
[0105] At 50℃, all indicators exhibited optimal equilibrium. Within the 2–3 hour dissolution period, the solution viscosity reached its peak plateau, the microsphere sphericity remained high, and the gel strength was at its maximum, indicating that the polymer chains were fully extended and the structure was intact. Considering both production efficiency and energy consumption, a 2-hour dissolution at 50℃ was ultimately selected as the standard preparation process for the outer matrix.
[0106] 3.3 Microfluidic coaxial crosslinking molding and crosslinking time screening
[0107] After the outer matrix was prepared and cooled to below 35°C, heat-sensitive compound vitamin powder was added, followed by the injection of an inner drug-loaded chitosan nanocluster dispersion. The mixture was then mixed at 3000 rpm under high shear to form a uniform micro-island-and-ocean composite colloidal solution. To achieve precise size control and structural solidification, the colloidal solution was transferred to a microfluidic granulation device and atomized and extruded through a 0.5 mm coaxial nozzle under high-pressure pulsed airflow, directly spraying it into a calcium chloride crosslinking bath. Upon contact with calcium ions, sodium alginate rapidly undergoes egg-box model coordination crosslinking, forming a gel shell and sealing the internal components.
[0108] Cross-linking time (i.e., the residence time of microspheres in a calcium bath) is a key variable determining the mechanical strength and enteric release characteristics of microspheres. If the cross-linking time is too short, the gel network is too loose and cannot resist the erosion of gastric acid; if the cross-linking time is too long, excessive calcium ion penetration leads to structural densification, which may hinder the intestinal release of functional factors.
[0109] A single-batch continuous sampling method was used. After microfluidic granulation was initiated, the collected nascent microspheres were continuously immersed in a cross-linking bath. At preset time points (3 to 30 minutes, 3-minute increments, 10 sets in total), a portion of the microspheres were removed and immediately immersed in a large amount of deionized water to remove free calcium ions from the surface and terminate the cross-linking reaction. A texture analyzer was used to perform compression tests on individual wet microspheres, recording the maximum force at which they ruptured to assess the strength of the gel skeleton. The microspheres were placed in simulated gastric fluid at pH 1.2 for 2 hours, and the rate of mass change after water absorption was measured. An excessively high expansion rate indicated a loose network, making acid osmosis leakage more likely. The microspheres treated with gastric fluid were then transferred to simulated intestinal fluid at pH 6.8, and the time required for complete disintegration and release of contents was recorded.
[0110] Test results are as follows Figure 7 As shown, the experimental data clearly depict the bidirectional effect of crosslinking degree on microsphere performance. In the initial stage of crosslinking, as calcium ions penetrate inward, the gel skeleton is rapidly strengthened, and the mechanical strength increases linearly. However, the expansion rate of microspheres in gastric juice is still relatively high at this stage, indicating that the acid resistance barrier has not been fully established. When the crosslinking time reaches the range of 15-18 minutes, the strength of microspheres exceeds 300g, and the gastric juice expansion rate drops to the ideal safe zone of less than 10%, indicating that a dense protective layer has been formed. At the same time, its disintegration time in intestinal juice is maintained within the golden window of 20-30 minutes, which avoids instantaneous release and ensures absorption timeliness. Although the strength increases slightly when the time is too long, the intestinal juice disintegration time is drastically extended to more than 40 minutes, resulting in the risk of release lag. Considering both protection and release, 18 minutes was finally selected as the standard crosslinking time.
[0111] 3.4 Screening of Microsphere Curing and Drying Processes
[0112] While wet gel microspheres possess a complete core-shell structure and physiological functions, their water content is typically over 90%, making them not only bulky and unsuitable for storage and transportation, but also highly susceptible to microbial growth and spoilage. Furthermore, the presence of moisture accelerates the hydrolysis and oxidation of active ingredients (such as ginsenosides and vitamins). Therefore, a suitable dehydration process is necessary to solidify the microspheres into a dry formulation.
[0113] 3.4.1 Drying process screening experiment
[0114] The thermal effects, interfacial tension, and mechanical stress during the drying process can easily damage the gel skeleton, leading to microsphere shrinkage, collapse, or deactivation of active substances. Therefore, it is necessary to screen existing drying processes for a technology that can efficiently dehydrate while preserving the microporous structure and bioactivity of the microspheres to the greatest extent possible.
[0115] Experimental group: Hot air drying (HAD): The microspheres were spread flat on a tray and placed in a 60℃ forced air drying oven, where hot air convection was used for mass transfer and heat transfer. Microwave vacuum drying (MVD): Pulsed heating drying is performed using a microwave magnetron (power density 2W / g) under a vacuum of 0.08MPa. Spray freeze drying (SFD): Wet microspheres are re-atomized and sprayed into liquid nitrogen for rapid freezing, followed by sublimation under vacuum. This method is commonly used to prepare ultrafine powders. Supercritical fluid drying (SCF): Supercritical carbon dioxide is used as an extractant to displace and remove moisture from the microspheres at 10 MPa and 35 °C. Vacuum Oven Drying (VOD): The microspheres are placed in a 45℃ vacuum chamber (0.09MPa) and the boiling point of water is lowered by negative pressure to achieve low-temperature evaporation. Vacuum freeze drying (FD): Microspheres are pre-frozen at -40℃ for 4 hours to form solid ice crystals, then sublimated under a vacuum of 40Pa, and finally desorption dried at 25℃.
[0116] The average particle size of the dried microspheres was measured using a laser particle size analyzer, and the absolute value of the difference between the average particle size and the initial wet-bulb particle size (850 μm) was calculated. A smaller difference indicates a more intact microsphere skeleton, without severe collapse or shrinkage; a larger difference indicates structural damage or pulverization. The dried microspheres were then immersed in 37°C warm water, and the time required for them to absorb water, swell, and return to their gel elastomer state was recorded. A shorter time indicates a more developed internal pore structure and stronger capillary action. Using vitamin C, the most heat-sensitive component, as a marker, the residual content in the dried product (theoretical value of 50 mg / g for initial feed) was determined by HPLC to assess the degree of damage to heat-sensitive components caused by the drying process.
[0117] The test results are as follows: Table 7
[0118] Supercritical drying offers advantages such as small particle size difference and high activity retention, but its equipment is extremely expensive and requires extremely high operating pressure, making large-scale industrial production difficult. While spray freeze-drying provides rapid rehydration and good activity retention, its high particle size difference indicates that the microspheres are completely pulverized into micron-sized powder, utterly destroying the core-shell microsphere structure. Vacuum freeze-drying, with its excellent overall performance, is therefore the preferred drying process.
[0119] After determining that vacuum freeze-drying was the optimal process, a standard drying procedure was established by directly referring to industry standards and considering the characteristics of this product (millimeter-sized wet gel microspheres) in order to standardize operations. First, pre-freeze at 40℃ for 4 hours (to ensure complete freezing); then, sublimation drying was carried out continuously for 24 hours at a vacuum of 20Pa and a shelf temperature of -10℃ to remove most of the free water; finally, the shelf temperature was adjusted to 25℃ for desorption drying for 4 hours (to remove bound water).
[0120] Example 4
[0121] This embodiment is based on the optimal components and process parameters selected from the previous embodiments, and refers to... Figure 8 The process flow diagram shown provides a complete method for preparing a compound hypoglycemic functional factor with multi-stage programmed release and intestinal targeted delivery, and comprehensively evaluates its microstructure, drug loading performance and in vitro release behavior.
[0122] S1. Constructing an inner membrane-adhesive nanocore
[0123] Dissolve 80g of chitosan (degree of deacetylation >90%) in 1000mL of 1% acetic acid solution and stir until completely dissolved to form a cationic matrix solution. Add 30g of ginseng extract (total saponins >80%) and 1.5g of a trace element mixture premixed according to the ratio of zinc lactate: chromium picolinate: selenium-enriched yeast ≈ 24:4:1.
[0124] The mixture was placed in an ultrasonic disperser and treated at 300W for 30 minutes to ensure that the active ingredients were fully embedded in the chitosan molecular chains. Subsequently, sodium tripolyphosphate solution (as an inducing agent) was slowly added dropwise under magnetic stirring until the solution became opalescent and self-assembled to form a dispersion of drug-loaded nanoclusters with positively charged surfaces.
[0125] S2. Preparation of the outer pH-sensitive smart gel matrix
[0126] 240g of sodium alginate (low viscosity) and 400g of β-glucan were dissolved in sufficient deionized water and stirred in a constant temperature water bath at 50℃ for 2 hours to obtain a homogeneous interpenetrating network matrix solution. After the solution cooled naturally to 35℃, 50g of compound vitamin powder (VB:VC=1:2) was added and slowly injected into the drug-loaded nanocluster dispersion prepared in step S1. The mixture was sheared and mixed at 3000rpm for 10 minutes to form a composite colloidal solution with micro-island and ocean structures.
[0127] S3, Microfluidic coaxial crosslinking molding
[0128] The composite colloidal solution was transferred to a microfluidic granulation device and atomized and extruded through a 0.5mm coaxial nozzle under the assistance of a high-pressure pulsed airflow. The droplets fell directly into a 3% calcium chloride crosslinking bath at 2-6℃. The residence time of the microspheres in the crosslinking bath was strictly controlled to 18 minutes to form a dense calcium alginate gel shell on the surface.
[0129] S4, Curing of multi-stage programmed release structure
[0130] The wet gel microspheres were filtered out and washed three times with sterile deionized water. They were then spread evenly on a freeze-drying tray and pre-frozen at -40°C for 4 hours; sublimation drying was carried out at 20Pa vacuum and -10°C shelf temperature for 24 hours; and finally desorption drying was carried out at 25°C shelf temperature for 4 hours to obtain the final compound hypoglycemic functional factor product.
[0131] The prepared product has a macroscopic particle size of 850±25μm (PDI<0.2); the internal structure, as shown by SEM, exhibits a sponge-like porous structure with spherical nanoclusters of 200~300nm embedded in the pore walls; the ginsenoside encapsulation rate is 94.5%; the β-glucan loading is 385mg / g; the gastric juice leakage rate is ginsenoside <3.5%; β-glucan <6.8%, and the microspheres remain intact with slight volume shrinkage and no disintegration is observed; the intestinal release disintegration time is 22 minutes, and the cumulative release rate of β-glucan within 30 minutes is >85%; the mucosal retention rate is >75% after 30 minutes of intestinal flushing.
[0132] In summary, this invention innovatively constructs a dual interpenetrating network structure consisting of a microscopic nanocore and a macroscopic gel shell, achieving multi-level programmed precise release through gastric protection, intestinal barrier, and mucosal targeting. The pH-responsive outer layer of calcium alginate gel effectively shields against gastric acid erosion and rapidly releases β-glucan in the intestine to construct a physical glucose-regulating barrier. The inner layer of chitosan nanoclusters utilizes its positive charge to target and adhere to the intestinal mucosa, deeply and slowly releasing ginsenosides and trace elements to regulate metabolism and repair functions. This process cleverly solves the pain points of poor stability and low absorption rate of active ingredients, as well as the difficulty in processing physical barrier agents, achieving a dual synergistic effect of physical barrier and physiological regulation, significantly improving overall hypoglycemic efficacy and bioavailability.
[0133] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A preparation process for a compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology, characterized in that, Includes the following steps: S1. Dissolve 70-90 parts by weight of chitosan to prepare a cationic matrix solution, then add 20-40 parts by weight of ginseng extract and a premixed trace element combination. The premixed trace element combination is composed of zinc lactate, chromium picolinate, and selenium-enriched yeast at a mass ratio of 20-24:3-5:0.5-1.
5. The mixture is ultrasonically dispersed at 200-400W for 25-35 minutes to ensure that the ginseng extract and the premixed trace element combination are fully dispersed in the chitosan matrix. Subsequently, sodium tripolyphosphate is added as an inducing solution to self-assemble and form a drug-loaded nanocluster dispersion. S2. Take 220-260 parts by weight of sodium alginate and 350-450 parts by weight of β-glucan, dissolve them together in deionized water, and stir at a constant temperature of 45-55℃ for 1-3 hours to form a homogeneous matrix solution; after the solution cools to below 35℃, add 40-60 parts by weight of compound vitamin powder, which is a premix of B vitamins and vitamin C at a mass ratio of 1:1.5-2.5, and then inject it into the drug-loaded nanocluster dispersion, and shear and mix to form a homogeneous composite colloidal solution; S3. The composite colloidal liquid is atomized and extruded into a crosslinking bath containing calcium chloride at 2~6℃ for 15~21 minutes. The coordination and crosslinking of calcium ions and sodium alginate will form a dense gel shell on the surface of the droplet, sealing the internal components and forming wet gel microspheres. S4. Take out and clean the wet gel microspheres, remove the moisture by vacuum freeze-drying while retaining the porous mesh structure inside the microspheres, and obtain the composite hypoglycemic functional factor.
2. The preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to claim 1, characterized in that, The induction solution is a sodium tripolyphosphate solution, the amount of chitosan is 80 parts by weight, and the amount of ginseng extract is 30 parts by weight.
3. The preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to claim 1, characterized in that, The amount of sodium alginate used is 240 parts by weight, and the amount of β-glucan used is 400 parts by weight.
4. The preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to claim 1, characterized in that, The ultrasonic power during the ultrasonic dispersion process is 300W, and the processing time is 30 minutes; the preparation temperature of the homogeneous matrix solution is 45~55℃, and the stirring time is 1~3 hours.
5. The preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to claim 1, characterized in that, The composite colloidal liquid is atomized and extruded through a 0.5mm coaxial nozzle under the assistance of a high-pressure pulsed gas flow into a crosslinking bath containing calcium chloride at 2~6℃. The concentration of calcium chloride is 2wt%~4wt%, and the high-pressure pulsed gas flow includes nitrogen and argon.
6. The preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to claim 1, characterized in that, The cross-linking time is 18 minutes; the cleaning medium for the microspheres after cross-linking is sterile deionized water, and the cleaning is performed no less than 3 times.
7. The preparation process of the compound hypoglycemic functional factor prepared by multi-stage programmed release and intestinal targeted delivery technology according to claim 1, characterized in that, The specific procedure for vacuum freeze drying is as follows: pre-freezing at -45~-35℃ for 3~5 hours; then sublimation drying at a vacuum of 10~300Pa and a shelf temperature of -20~-5℃ for 20~30 hours; and finally desorption drying at a shelf temperature of 20~30℃ for 3~5 hours.
8. A compound hypoglycemic functional factor prepared by any one of the preparation processes according to claims 1 to 7, characterized in that, The prepared compound hypoglycemic functional factor is a gel microsphere, which includes an outer gel matrix and chitosan drug-loaded nanoclusters dispersed in the outer gel matrix. The outer gel matrix is formed by calcium alginate and β-glucan, which remains contracted and dense in the gastric acid environment and swells and disintegrates in the intestinal fluid environment to release β-glucan and compound vitamin powder. The chitosan drug-loaded nanoclusters are loaded with ginseng extract and trace elements, which can adhere to the intestinal mucosa and achieve sustained release of active ingredients.